2020
DOI: 10.3390/ijerph17134749
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality in Passivhaus Dwellings: A Literature Review

Abstract: Indoor air quality (IAQ) is a critical consideration in airtight buildings that depend on mechanical ventilation, such as those constructed to the Passivhaus standard. While previous reviews of IAQ on Passivhaus-certified buildings foccused on offices, this study examines residential buildings. A summary of data collection methods and pollutant concentrations is presented, followed by a critical discussion of the impact of Passivhaus design strategies on IAQ. This review indicates that IAQ in Passivhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 90 publications
(206 reference statements)
0
24
0
Order By: Relevance
“…Ventilation has a major impact on indoor air quality (IAQ) and comfort [32,33]. Mechanical ventilation systems that are properly operated and maintained eliminate pollutants, improve IAQ and minimize the incidence of comfort-and health-related problems, in particular in new and air-tight buildings [34,35]. They are also highly effective in reducing particle pollution in residential buildings [36].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Ventilation has a major impact on indoor air quality (IAQ) and comfort [32,33]. Mechanical ventilation systems that are properly operated and maintained eliminate pollutants, improve IAQ and minimize the incidence of comfort-and health-related problems, in particular in new and air-tight buildings [34,35]. They are also highly effective in reducing particle pollution in residential buildings [36].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…39 Despite advances in measurement technologies, a recent review of Passivhaus studies indicated very few studies included physical IAQ measurements beyond CO 2 . 40,41 This indicates a lack of comprehensive UK-based IAQ studies on lowenergy dwellings including apartments. 42 Meanwhile, the recent IEA-EBC Annex 68, 'Indoor Air Quality Design and Control in Low Energy Residential Buildings', has contributed to the definition of IAQ metrics, identified key pollutants from previous studies and developed guidelines for the design and operational strategy of domestic dwellings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, advanced and efficient HVAC systems can offer energy savings and benefits to occupants [45,46]. Air quality impacts the health and comfort of building occupants [47], and passive houses have higher air-change rates than that of the minimum building code requirement and achieve limited energy consumption [48][49][50][51]. This could become a driving force for increased competitiveness through approaches to implementation for sustainable growth.…”
Section: Introductionmentioning
confidence: 99%